Human Factor in Decision-Making in Simulation Model of Transportation System and Approaches to Its Modelling - Michal Zarnay (Communications - Scientific letters of the University of Zilina, 2004)
The article deals with human factor in decision-making in simulation model of transportation system. It points to the difference between the management in reality and in a model, where it is more difficult to represent the human thinking. The consequence of this is a higher probability of deadlock appearances that can be developed after operation has deflected from the plan. The effort to minimize the operation deviations leads to processing larger amount of information and to more complicated decision-making algorithms, which makes the simulation model more complicated and slower. The task of the developer is to set the level of details in the decision-making subsystem.In the end of the article, few different approaches to the modelling of human decision-making are mentioned.